Kinerja Aparatur Sipil Negara Badan Pengembangan Sumber Daya Manusia Daerah Provinsi Sulawesi Utara Dalam Pelayanan Publik - Paulus Tamaka (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
Performance achievement is the result of work that has been achieved by an employee in carrying out their duties and functions. Performance can be a measure of the success of a regional apparatus or agency in carrying out its duties and functions. For this reason, it is necessary to carry out an apparatus performance appraisal, this assessment is intended to see whether the work results of the apparatus are in accordance with what is expected. One of the problems that occurs in the Regional Human Resources Development Agency is the slow service provided by the apparatus, one of the causes is that sometimes they do not follow the service procedures that have been set, such as not meeting complete requirements, and sometimes there are several letter services that require signature from the Head of the Agency so that when the Head of the Agency is not at the place of an affair, he must wait for the signature of the Head of the Agency so that the service is a little slow and other problems are due to no delegation. The purpose of this study was to determine and describe the performance of the State Civil Apparatus in Public Service at the Regional Human Resources Development Agency. To achieve this goal, the method used in this research is qualitative. This type of research is a qualitative descriptive study. Data collection was carried out through interviews, observation and documentation. The data sources used are primary and secondary data.In this study, the conclusion is that the performance of the state civil apparatus in public services is generally good and is heading to a better level. Based on the performance indicators used, it can be said that the performance of the State Civil Apparatus is quite good. However, more or less the apparatus must improve and further improve their performance in public services.Performance achievement is the result of work that has been achieved by an employee in carrying out their duties and functions. Performance can be a measure of the success of a regional apparatus or agency in carrying out its duties and functions. For this reason, it is necessary to carry out an apparatus performance appraisal, this assessment is intended to see whether the work results of the apparatus are in accordance with what is expected. One of the problems that occurs in the Regional Human Resources Development Agency is the slow service provided by the apparatus, one of the causes is that sometimes they do not follow the service procedures that have been set, such as not meeting complete requirements, and sometimes there are several letter services that require signature from the Head of the Agency so that when the Head of the Agency is not at the place of an affair, he must wait for the signature of the Head of the Agency so that the service is a little slow and other problems are due to no delegation. The purpose of this study was to determine and describe the performance of the State Civil Apparatus in Public Service at the Regional Human Resources Development Agency. To achieve this goal, the method used in this research is qualitative. This type of research is a qualitative descriptive study. Data collection was carried out through interviews, observation and documentation. The data sources used are primary and secondary data.In this study, the conclusion is that the performance of the state civil apparatus in public services is generally good and is heading to a better level. Based on the performance indicators used, it can be said that the performance of the State Civil Apparatus is quite good. However, more or less the apparatus must improve and further improve their performance in public services.Prestasi Kinerja adalah merupakan hasil kerja yang telah dicapai oleh seseorang pegawai dalam menjalankan tugas dan fungsinya. Kinerja dapat menjadi sebuah ukuran keberhasilan suatu perangkat daerah atau instansi dalam menjalankan tugas dan fungsinya. Untuk itu perlu dilakukan penilaian kinerja aparatur, penilaian ini dimaksudkan untuk melihat apakah hasil kerja dari aparatur sudah sesuai dengan apa yang diharapkan. Salah satu masalah yang terjadi di Badan Pengembangan Sumber Daya Manusia Daerah yaitu Lambatnya pelayanan yang diberikan aparatur, salah satu penyebabnya yaitu yang terkadang tidak mengikuti prosedur pelayanan yang telah ditetapkan, seperti tidak memenuhi persyaratan yang lengkap, dan terkadang ada beberapa pelayanan surat yang diperlukan tanda tangan dari Kepala Badan sehingga pada saat Kepala Badan tidak ada ditempat suatu urusan tersebut harus menunggu tanda tangan Kepala Badan sehingga pelayanan sedikit lambat serta masalah yang lainnya karena tidak ada pendelegasian. Adapun Tujuan penelitian ini adalah untuk mengetahui dan mendeskripsikan Kinerja Aparatur Sipil Negara Dalam Pelayanan Publik di Badan Pengembangan Sumber Daya Manusia Daerah. Untuk mencapai tujuan tersebut metode yang digunakan dalam penelitian ini adalah kulitatif. Jenis penelitian ini adalah penelitian deskriptif kualitatif. Pengumpulan data dilakukan dengan melalui wawancara, observasi dan dokumentasi. Sumber data yang digunakan berasal dari data primer dan sekunder. Dalam penelitian ini diperoleh kesimpulan bahwa kinerja Aparatur sipil negara dalam Pelayanan Publik secara umum dapat dikatakan baik dan sedang menuju pada level yang lebih baik lagi. Berdasarkan indikator kinerja yang digunakan dapat dikatakan bahwa kinerja Aparatur Sipil Negara sudah cukup baik. Namun sedikit banyaknya aparatur harus lebih membenahi dan lebih meningkatkan lagi kinerjanya dalam pelayanan publik.